Phase I/II study on cytarabine and idarubicin combined with escalating doses of clofarabine in newly diagnosed patients with acute myeloid leukaemia and high risk for induction failure (AMLSG 17‐10 CIARA trial). (30th October 2018) - Krauter, Jürgen; Fiedler, Walter; Schlenk, Richard F.; Paschka, Peter; Thol, Felicitas; Lübbert, Michael; Wattad, Mohammed; Verbeek, Mareike; Könecke, Christian; Neuhaus, Barbara; Papkalla, Armin; Kebenko, Maxim; et al.
Summary: This open‐label, multicentre phase I/II study determined the maximum tolerated dose (MTD), safety and efficacy of clofarabine administered with cytarabine and idarubicin in newly diagnosed acute myeloid leukaemia (AML) patients lacking favourable genetic aberrations. The MTD was 30 mg/m 2 clofarabine for patients below and above 60 years. The most frequently reported grade 3–4 non‐haematological adverse events were infectious and gastrointestinal toxicities. Complete remission (CR)/CR with incomplete recovery rate was 67%. Allogeneic haematopoietic cell transplantation in first remission was feasible in a high proportion of younger AML patients and probably contributed to the favourable outcome compared to historical controls.